AKUNTABILITAS PELAYANAN PUBLIK DALAM PEMBUATAN TANDA NOMOR KENDARAAN BERMOTOR DI KANTOR SAMSAT KABUPATEN SINJAI - Nurhidayah, Nurhidayah; Muhiddin, Amir; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The purpose of this study is to find out how public service accountability in the making of the auto sign number in sinjai county's samsat office. The type of case study that will provide an overview or a detailed phenomenon. Data collection with observation, interviews, documentation. Research conducted at sinjai county's samsat office on public service accountability are four criteria: procedures, costs, time frame, and responsiveness. According to the results, public service accountability in the sign for the motor vehicle number (TNKB) in sinjai county's samsat office has been well under way and is implementing the prime service procedure of SOP, While there are still a few constrakes such as the cost tariffs and the lack of attention to the target, the samsat office in sinjai district is currently assessed, according to the rules set in sinjai district's samsat area.